Reassessing the Ne Bis in Idem Principle in Administrative Sanctions within the Financial Sector - Siti Mutiah Rahmadanti (Veteran Law Review, 2025)
Indonesia’s financial regulators increasingly rely on administrative sanctions, heightening the risk that overlapping mandates may yield duplicative penalties for the same misconduct. This paper examines the application of the ne bis in idem principle to administrative enforcement within the financial sector and evaluates the extent to which the Una Via mechanism introduced by the 2023 Financial Sector Law mitigates “double punishment.” Using a normative juridical method that combines statutory, conceptual, and case approaches, we develop a doctrinal test for “the same offence” (fact pattern, protected legal interest, and punitive purpose) and adapt the Engel criteria to identify when administrative fines are criminal-like. A complementarity-versus-duplication framework is proposed for OJK–IDX coordination, supported by offsetting and single-cap rules to preserve proportionality. Comparative insights from the EU and ASEAN underscore the need for integrated procedures and total-sanction proportionality control. We recommend a triage MoU, a joint case registry, and a no-piling-on policy across OJK, IDX, and the Ministry of Finance to safeguard legal certainty while maintaining credible deterrence.